Beta-mangostin demonstrates apoptogenesis in murine leukaemia (WEHI-3) cells in vitro and in vivo - Omer F.A.A.; Hashim N.M.; Ibrahim M.Y.; Aldoubi A.F.; Hassandarvish P.; Dehghan F.; Nordin N.; Karimian H.; Salim L.Z.A.; Abdulla M.A.; Al-Jashamy K.; Mohan S. (BioMed Central Ltd., 2024)
Index by Scopus ,WOS & ERA